Information System Strategic Planning at PT XYZ Using Ward and Peppard Model in The Stock Trading Sector in Indonesia - Achsan, Fathanal (Universitas Multi Data Palembang, 2024)
The progress of technology has caused transformative shifts in several financial sectors, stock trading included. Statistics from the Indonesian Central Securities Depository (KSEI) show that in 2022(KSEI, 2022), daily stock transaction frequency averaged 1.31 million times, with a Daily Transaction Value (DTV) averaging Rp 14.7 trillion. This marked a 10% rise from the prior year (2021). This journal recognize growth potential in this sector, and use a study case from PT XYZ to align with this trend and revise the strategy to expand the market and retail investors. Hence, a robust information system strategy is crucial. This strategy will not only enable PT XYZ's entry into the Online Trading (OT) sector but also improve its competitiveness and overall profitability. This journal show how to craft an information system strategic plan using the Ward and Peppard model and supporting tools such as Political, Economic, Social, Technological (PEST), IT Balanced score card (IT BSC), Strengths, Weaknesses, Opportunities, and Threats (SWOT), Mc Farlan and Critical success factor (CSF) analisys.